Prevention of invasive ventilation (PRiVENT): a prospective, mixed-methods interventional, multicentre study with a parallel comparison group$dstudy protocol - Michels-Zetsche, Julia D.; Meis, Jan; Sturm, Noemi; Bornitz, Florian; Schumann, Selina von; Weis, Aline; Neetz, Benjamin; Bentner, Martina; Forstner, Johanna; Litke, Nicola; Wensing, Michel; Erdmann, Stella; et al. (BMC health services research, 2023)
Invasive mechanical ventilation (IMV) is a standard therapy for intensive care patients with respiratory failure. With increasing population age and multimorbidity, the number of patients who cannot be weaned from IMV increases, resulting in impaired quality of life and high costs. In addition, human resources are tied up in the care of these patients.
The PRiVENT study group: Felix JF Herth, Franziska Christina Trudzinski, Julia Dorothea Michels, Michael Müller, Benjamin Neetz, Gabriele Iberl, Beatrice Müller, Jan Meis, Martina Bentner, Elena Biehler, Thomas Fleischhhauer, Johanna, Forstner, Gerhard Fuchs, Nicola Litke, Markus Qreini, Selina von Schumann, Noemi Sturm, Joachim Szecsenyi, Aline Weis, Michael Wensing, Janina Schubert-Haack, Timm Frerk, Anja Klingenberg, Alex Kempa, Biljana Joves, Andreas Rheinhold, Claus Neurohr, Alessandro Ghiani, Nina Lutz, Swenja Walcher, Konstantinos Tsitouras, Joanna Paderewska, Selina Briese, Armin Schneider, Christoph Andritschky, Patrick Gehrig, Joachim Sugg, Susanne Hirschmann, Simone Britsch, Christa Straub, Claude Jabbour, Michael Hahn, Jörg Krebs, Peter-Tobias Graf, Petra Denzer, Mascha O. Fiedler, Miriane Bomeken, Sebastian Stier, Tom Terboven, Uta Merle, Jens Regula, Jens Müller, Ute Oltmanns, Marcus Hennersdorf, Neslihan Satir, Mathias Borst, Brigitte Mayer, Wolfgang Reikow, Markus Kredel, Konstantin Frey, Holger Wolff, Florian Seidlitz, Stefanie Bientzle, Boris Nohé, Sebastian Allgäuer, Alexej Schöpp, Christoph Schlegel, Imke Hübner, Andrezj Kuzniar, Helene Häberle, Reimer Riessen, Benjamin Schempf, Ingo Rebenschütz, Andreas Straub, Marc Kollum, Markus Winter, Paul Hartveg, Andreas Junginger, Helmut Beck, Mathias Vogel
Gesehen am 24.04.2023